2020
DOI: 10.1039/d0ta04750c
|View full text |Cite
|
Sign up to set email alerts
|

Controlled colloidal metal nanoparticles and nanoclusters: recent applications as cocatalysts for improving photocatalytic water-splitting activity

Abstract: This review introduces the importance of controlled colloidal NPs/NCs in research on water-splitting photocatalysis by summarizing the existing research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 246 publications
(263 reference statements)
1
47
0
Order By: Relevance
“…The unique characteristics of the clusters render them suitable for use as photosensitizer materials. Indeed, thiolate‐protected gold clusters have been shown to serve as photosensitizers in singlet oxygen ( 1 O 2 ) generation, [16] solar cells, [17, 18] and photocatalysis [19] . Furthermore, a recent study on the photosensitization of 1 O 2 using [Au 25 (SR) 18 ] − has confirmed the formation of an excited triplet state of the cluster [20] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The unique characteristics of the clusters render them suitable for use as photosensitizer materials. Indeed, thiolate‐protected gold clusters have been shown to serve as photosensitizers in singlet oxygen ( 1 O 2 ) generation, [16] solar cells, [17, 18] and photocatalysis [19] . Furthermore, a recent study on the photosensitization of 1 O 2 using [Au 25 (SR) 18 ] − has confirmed the formation of an excited triplet state of the cluster [20] .…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, thiolate-protected gold clusters have been shown to serve as photosensitizers in singlet oxygen ( 1 O 2 ) generation, [16] solar cells, [17,18] and photocatalysis. [19] Furthermore, a recent study on the photosensitization of 1 O 2 using [Au 25 (SR) 18 ] À has confirmed the formation of an excited triplet state of the cluster. [20] To the best of our knowledge, the use of atomically precise noble metal clusters as triplet sensitizers in TTA-UC has not been explored to date.…”
mentioning
confidence: 93%
“…18 This Au 25 was attached to the alumina sphere after stirring in water in a manner similar to that described in previous studies. [18][19][20] In particular, Au 25 ðSGÞ 18 clusters were adsorbed on the alumina sphere by mixing an aqueous solution containing Au 25 ðSGÞ 18 with an aqueous solution of alumina sphere (600 mg) for 2 h at room temperature (∼20°C). The total volume of the aqueous solution was fixed at 200 mL, and the mixing ratio of the Au 25 ðSGÞ 18 clusters to the alumina sphere was fixed at 0.05, 0.1, or 0.2 wt.…”
Section: Au Cluster Attachmentmentioning
confidence: 99%
“…Particularly, the alkyl groups and their position (with respect to metal binding site) on the aromatic ring of the ligand are found to have a profound influence, which often dictate the size and structure of NCs [12a, 13] . Typical ligands used for stabilizing NCs are thiols, [14] phosphines, [15] hydrides, [16] alkynes [17] and/or their combinations [5b, 12b] . Post synthetic ligand‐exchange has also been found to result in the NCs of novel size and molecular structure [18] .…”
Section: Introductionmentioning
confidence: 99%
“…The size‐ and structure‐property relationships in NCs are highly desirable to design NC‐based materials for prospective applications in catalysis and energy conversion, which requires well‐controlled size, composition, electronic charge and geometric and electronic structure [12b, 21] . Unfortunately, there are no hard and fast rules to attain NCs of desired characteristics since the molecular mechanism of the formation of NCs is still unknown.…”
Section: Introductionmentioning
confidence: 99%